2004
DOI: 10.1152/jn.00571.2003
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Dynamics of Binocular Disparity Processing in the Central Visual Pathway

Abstract: . To solve the stereo correspondence problem (i.e., find the matching features of a visual scene in both eyes), it is advantageous to combine information across spatial scales. The details of how this is accomplished are not clear. Psychophysical studies and mathematical models have suggested various types of interactions across spatial scale, including coarse to fine, fine to coarse, averaging, and population coding. In this study, we investigate dynamic changes in disparity tuning of simple and complex cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 49 publications
3
29
0
Order By: Relevance
“…In contrast, Zohary et al (1990) reported increased orientation discriminability as the integration window increased from 60-100 ms, and Ringach et al (1997) reported significant time dependency of orientation tuning using a finer-grained temporal analysis (10 vs. 50 ms bins). In the domain of stereopsis, Menz andFreeman (2003, 2004) showed that binocular disparity tuning in cat visual cortex sharpens with time, consistent with coarse-to-fine processing.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…In contrast, Zohary et al (1990) reported increased orientation discriminability as the integration window increased from 60-100 ms, and Ringach et al (1997) reported significant time dependency of orientation tuning using a finer-grained temporal analysis (10 vs. 50 ms bins). In the domain of stereopsis, Menz andFreeman (2003, 2004) showed that binocular disparity tuning in cat visual cortex sharpens with time, consistent with coarse-to-fine processing.…”
Section: Discussionmentioning
confidence: 76%
“…In the visual system, LGN (lateral geniculate nucleus) neurons temporally decorrelate in response to natural movies, but not to white noise, by a process involving linear temporal filtering characteristics of neurons (Dan et al 1996). In the visual cortex, many previous studies have explored the temporal dynamics of individual cell responses, especially in area V1 (see, e.g., Albrecht et al 2002;Bredfeldt and Ringach 2002;Celebrini et al 1993;DeAngelis et al 1993;Jones and Palmer 1987;Mazer et al 2002;Menz andFreeman 2003, 2004;Müller et al 2001;Ringach et al 1997;Shapley et al 2003) and in the inferior temporal cortex (Edwards et al 2003;Keysers et al 2001;Oram and Perrett 1992;Tovée et al 1993). Recently, Müller et al (2001) analyzed the temporal dynamics of the signal-tonoise ratio in area V1 of the anesthetized monkey and found that V1 cells convey much more information during the initial transients than during later periods of the same duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, meaningful changes in tuning properties can occur on much shorter time scales (Ringach et al, 1997;Cottaris and De Valois, 1998;Menz and Freeman, 2004), prompting us to examine the evolution of spatial reference frames over time. For each neuron, we computed DI within a 100 ms window that was stepped through the 2 s stimulus period in increments of 50 ms. We then plotted the mean DI (ϮSEM) across neurons for each time point, separated by stimulus condition (Fig.…”
Section: Time Course Of Reference Framesmentioning
confidence: 99%
“…It is also important to note that combining excitation at one scale with inhibition over a broader scale has the effect of 'sharpening' the disparity tuned response of the sum. Consequently, the responses of single neurons do move from coding coarser scales to finer scales over a period of 20-50 ms [7,[26][27][28]. The early coarse-to-fine algorithms imagined this combination happening at a stage after the initial binocular filtering [15].…”
Section: Extending the Energy Modelmentioning
confidence: 99%